2017
DOI: 10.1021/acs.est.6b03556
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Iodide-Mediated Ozone Deposition and Halogen Chemistry on Surface Ozone Concentrations Across the Continental United States

Abstract: The air quality of many large coastal areas in the United States is affected by the confluence of polluted urban and relatively clean marine airmasses, each with distinct atmospheric chemistry. In this context, the role of iodide-mediated ozone (O) deposition over seawater and marine halogen chemistry accounted for in both the lateral boundary conditions and coastal waters surrounding the continental U.S. is examined using the Community Multiscale Air Quality (CMAQ) model. Several nested simulations are conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Chlorine chemistry was implemented into the WRF-Chem model (Lowe et al, 2015;Li et al, 2016) and into the Community Multi-scale Air Quality (CMAQ) model (Sarwar et al, 2014) to study the formation of nitryl chloride (ClNO 2 ) from the uptake of dinitrogen pentoxide (N 2 O 5 ) on aerosols containing chloride. Moreover, bromine and iodine chemistry was implemented in CMAQ in Gantt et al (2017) and Sarwar et al (2015), where the impact of iodide-mediated O 3 deposition on surface ozone concentrations was studied, and in the recent work of Muñiz-Unamunzaga et al (2018), which concluded that oceanic halogens and dimethyl sulfide (DMS) emissions need to be included into the regional models to accurately reproduce the air quality in coastal cities.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine chemistry was implemented into the WRF-Chem model (Lowe et al, 2015;Li et al, 2016) and into the Community Multi-scale Air Quality (CMAQ) model (Sarwar et al, 2014) to study the formation of nitryl chloride (ClNO 2 ) from the uptake of dinitrogen pentoxide (N 2 O 5 ) on aerosols containing chloride. Moreover, bromine and iodine chemistry was implemented in CMAQ in Gantt et al (2017) and Sarwar et al (2015), where the impact of iodide-mediated O 3 deposition on surface ozone concentrations was studied, and in the recent work of Muñiz-Unamunzaga et al (2018), which concluded that oceanic halogens and dimethyl sulfide (DMS) emissions need to be included into the regional models to accurately reproduce the air quality in coastal cities.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al, 2016Lu et al, , 2018Zhou et al, 2015), atmospheric composition (e.g. Ganzeveld et al, 2009;Saiz-Lopez et al, 2014;Sherwen et al, 2016a), and air-quality prediction (e.g. Luhar et al, 2017Luhar et al, , 2018Sarwar et al, 2015;Sherwen et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of I − with ozone in the sea-surface micro-layer removes ozone from the atmosphere (dry deposition) (Ganzeveld et al, 2009) and results in the emission of inorganic iodine (HOI and I 2 ) into the atmosphere (Carpenter et al, 2013), which can subsequently catalytically destroy ozone (Chameides and Davis, 1980). A number of model studies have discussed the impact of oceansourced iodine on atmosphere composition in the context of air quality (Gantt et al, 2017;Sarwar et al, 2016;Sherwen et al, 2017b), climate (Sherwen et al, 2017b;Saiz-Lopez et al, 2012), aerosols (Sherwen et al, 2017a), and stratospheric ozone (Saiz-Lopez et al, 2015). These atmospheric modelling studies have used relatively simple parameterisations for predictions of sea-surface iodide.…”
Section: Introductionmentioning
confidence: 99%